Idris Enterprise (Sambal Hitam Pahang) / Hazel Lasius... [et al.] - Hazel, Lasius; Avon Biug, Teresita; Azmi, Nurul Suhada; Zulkiple, Siti Aisyah; Qusham, Lailatul Jaaizah; Badrulhisyam, Nursyakirah (2019)
Malaysians have always been close to their traditional cmsme, hence our company introduced our own product of Samba! Hitam Pahang, by using our own unique recipe which includes no chemical preservatives and made with high quality of raw materials. This will also become a solution mostly for the students that is studying overseas, to satisfy their craves for the taste of homemade cooking especially the traditional cuisine. Also our company came out with a great product packaging in which benefits the consumers in flexibility of bringing this product just anywhere and it is readily available to be consumed straight from the resealable plastic packaging without the need of trrerring it to another cont amer.